2020
DOI: 10.1002/cb.1851
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and consumer belonging: Influences on product evaluations

Abstract: Consumers have a fundamental need to belong. Prior research has examined the compensatory mechanisms that consumers use to restore belongingness when they have a low sense of belonging. However, research has yet to adequately understand the influence that having a high sense of belonging has on consumption behavior. Thus, three studies are conducted to address this gap in the literature, specifically examining religiosity as a source of consumers' high sense of belonging. Study 1A identifies that religiosity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
(111 reference statements)
1
5
0
Order By: Relevance
“…Hence, it also verifies the role of religion to bridge people’s minds and economic and social values. This study confirmed preliminary studies that religion is still an essential key point among people to adopt a product and service rather than materialism (Minton and Liu, 2020; Nugraha and Widyaningsih, 2021; Zakaria, et al , 2021). However, religiosity is less significant than materialism to influence the people to adopt a product that complies with the religious brand in India (Islam and Chandrasekaran, 2019), Indonesia (Junaidi et al , 2021) and Malaysia (Jan and Shafiq, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hence, it also verifies the role of religion to bridge people’s minds and economic and social values. This study confirmed preliminary studies that religion is still an essential key point among people to adopt a product and service rather than materialism (Minton and Liu, 2020; Nugraha and Widyaningsih, 2021; Zakaria, et al , 2021). However, religiosity is less significant than materialism to influence the people to adopt a product that complies with the religious brand in India (Islam and Chandrasekaran, 2019), Indonesia (Junaidi et al , 2021) and Malaysia (Jan and Shafiq, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Commitment has an important role in describing the association between customers and companies toward specific products and services (Islam and Rahman, 2017; Keiningham et al , 2015; Minton and Liu, 2020; Tabrani et al , 2018). It occurred toward two essential dimensions: religiosity and psychology (Abalkhail, 2021; Keiningham et al , 2015).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Consequently, minority consumer groups may question their sense of belonging to the environment or brand within which they experience the threat (Cheryan et al, 2009; Georgeac & Rattan, 2023; Rattan et al, 2018). A low sense of belonging may negatively impact engagement with brands (Cheung & Lee, 2012), participation in brand communities (Zhao et al, 2012), product evaluations (Minton & Liu, 2021), satisfaction (Hahm et al, 2018), likelihood to spread electronic word‐of ‐mouth (Chu et al, 2019), and purchase intentions (Schultz et al, 2022).…”
Section: Key Literaturementioning
confidence: 99%
“…Although vice product industries are among the most profitable businesses in the world, marketing research on vice product consumption has yet to grow compared to research on common consumer goods (see Minton & Liu, 2020). Our review of current literature found that there is significantly fewer research on vice products (both substance and behavioural vice) compared to common consumer goods in the marketing literature; even fewer (studies) examine the religious impact on vice product consumption versus common consumer goods.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous studies have investigated how religiosity can influence consumer behaviours and their consumption choices (e.g., Casabayó et al., 2020; Coşgel & Minkler, 2004; Elhoushy & Jang, 2020; Wang & Wong, 2020); consistent findings have emerged over time (Lam, 2006; Nonnemaker et al., 2006; Shaharudin et al., 2010). For example, religion influences a sense of belonging and consumer product evaluations (Minton & Geiger‐Oneto, 2020; Minton & Liu, 2020; Wang & Wong, 2020). Higher religiosity is associated with higher brand loyalty and more conservative purchase decisions (Delener, 1990; Essoo & Dibb, 2004; Tang & Li, 2015).…”
Section: Introductionmentioning
confidence: 99%